Rational design of a facile camphor-based fluorescence turn-on probe for real-time tracking of hypochlorous acid in vivo and in vitro. Issue 10 (5th May 2022) - Wang, Zhonglong; Zhang, Yan; Liang, Yueyin; Li, Mingxin; Meng, Zhiyuan; Gong, Shuai; Yang, Yiqin; Xu, Xu; Wang, Shifa
Abstract : A novel camphor-based fluorescence turn-on probe with high selectivity and sensitivity was developed for HClO detection, and it was successfully employed for real-time imaging of exogenous and endogenous HClO in living cells as well as in living zebrafish. Abstract : A simple yet highly effective camphor-derived fluorescent probe named 3-(anthracen-9-ylmethylene)-1, 7, 7-trimethylbicyclo[2.2.1]heptan-2-one oxime (ATHO ) was developed based on an oxime recognition receptor and anthracene fluorophore. The probe ATHO exhibited a remarkably enhanced fluorescence response to HClO (∼7.2 fold). Meanwhile, this probe exhibited a low detection limit (0.118 μM), ultrafast response time (within seconds), excellent photostability (>260 min), wide linear range (0–180 μM), low probe concentration (2 μM), and high selectivity toward HClO over various interfering species. The sensing mechanism of the probe ATHO for HClO was supported by HRMS analysis and theoretical calculations. Furthermore, the probe ATHO was utilized to quantitatively determine HClO levels in environmental water samples. Additionally, the biological imaging of the probe ATHO for exogenous and endogenous HClO was successfully demonstrated in vitro and in vivo .